777. Travel Destination, Demographics, and Underlying Medical Conditions Among Travelers Seeking Yellow Fever Vaccination at a Large Academic Medical Center in the U.S. (31st December 2020) - Bandali, Mehdi; Than, Kimlien; Schultz, Jonathan; McGregor, Donna V; Archuleta, Solana; Chadalawada, Sindhu; Mundo, William; Chastain, Daniel B; Franco-Paredes, Carlos; Reno, Elaine; Henao-Martinez, Andres
Abstract: Background: Yellow fever (YF) vaccine has the potential to cause viscerotropic and neurotropic disease in at-risk individuals. Screening patients is necessary to prevent vaccine-related life-threatening complications. We lack data on the clinical features of patients seeking YF vaccination. We aim to describe the characteristics of a cohort of patients receiving the YF vaccine before travel. Methods: A retrospective analysis of 964 patients receiving the YF vaccine (Stamaril®) from Oct 2016 to Jul 2019 was performed at the University of Colorado Hospital in the United States. Percentages, means, and standard deviations were calculated. A multivariate logistic regression model was built to evaluate the association between receiving YF vaccination less than 10 days before departure and visiting friends and relatives (VFR). Results: The average age of patients was 39 ± 18 years with a range of 9 months to 83 years. Patients who were 60 years of age and older represented 17%. Women consisted of 52%, and most of the patients were Caucasians (64%). Patients reported traveling to Africa (57%) or South America (40%). The primary destination for patients overall was Kenya (19%), Uganda (11%), and Tanzania (11%) in Africa; and Peru (14%) and Brazil (13%) in South America. The most common reasons for travel included leisure (44%), VFR (18%), and mission trips (10%). Comorbidities included a history of hematologic disorders (4%), HIV infection (2%), and diabetes mellitus (3%). The average duration between vaccine administration and travel was 43 days. Those visiting friends and relatives were 2 times more likely to receive the YF vaccination less than 10 days before departure. Table 1. A cohort of patients receiving the Yellow Fever vaccine at the University of Colorado Hospital. Figure 1. Heat map of destinations among patients receiving the YF vaccine. Figure 2. Reasons for travel among patients receiving the YF vaccine (n=964). Conclusion: Identifying the type of travel, itinerary, and underlying medical conditions allows providers to administer the YF vaccine to travelers safely. There is a need to identify strategies to improve the timing of YF vaccination among travelers visiting friends and relatives. Disclosures: All Authors : No reported disclosures